2009
DOI: 10.1523/jneurosci.5473-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Differential Susceptibility to Excitotoxic Stress in YAC128 Mouse Models of Huntington Disease between Initiation and Progression of Disease

Abstract: Huntington disease (HD) is a neurodegenerative disorder caused by an expanded CAG tract in the HD gene. Polyglutamine expansion of huntingtin (htt) results in early, progressive loss of medium spiny striatal neurons, as well as cortical neurons that project to the striatum. Excitotoxicity has been postulated to play a key role in the selective vulnerability of striatal neurons in HD. Early excitotoxic neuropathological changes observed in human HD brain include increased quinolinate (QUIN) concurrent with prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
138
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(156 citation statements)
references
References 86 publications
18
138
0
Order By: Relevance
“…Finally, we also found that chronic treatment with the highly selective M 4 PAM VU0467154 prevents or delays the onset of deficits in both striatal glutamatergic and dopaminergic signaling that are observed in 5-mo-old YAC128 mice and also improves motor symptoms detected at this age. An early increase in corticostriatal glutamatergic transmission has been described previously in multiple mouse models of HD (8,(11)(12)(13)(14). These changes could contribute to early vulnerability of SPNs to excitotoxicity and synaptic alterations (11).…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Finally, we also found that chronic treatment with the highly selective M 4 PAM VU0467154 prevents or delays the onset of deficits in both striatal glutamatergic and dopaminergic signaling that are observed in 5-mo-old YAC128 mice and also improves motor symptoms detected at this age. An early increase in corticostriatal glutamatergic transmission has been described previously in multiple mouse models of HD (8,(11)(12)(13)(14). These changes could contribute to early vulnerability of SPNs to excitotoxicity and synaptic alterations (11).…”
Section: Discussionmentioning
confidence: 54%
“…An early increase in corticostriatal glutamatergic transmission has been described previously in multiple mouse models of HD (8,(11)(12)(13)(14). These changes could contribute to early vulnerability of SPNs to excitotoxicity and synaptic alterations (11).…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations